Analysis of Attitude Assessment in Islamic Religious Education in Elementary Schools - Siti Mahmudah; Alfan Shafrizal (IAIN Palopo, 2022)
Learning Islamic religious education can not be separated from the results of learning or assessment. The assessment of Islamic religious education subjects did not describe students' attitudes. This study aims to assess attitudes toward Islamic religious education in elementary schools. This study used the descriptive qualitative method. Sources of data obtained from primary data and secondary data. Primary data are from 19th-grade and 5th-grade students.Meanwhile, secondary data includes principals, teachers, parents, and classmates. Data collection techniques used are observation, interviews, and documentation. The collected data will be processed using inductive qualitative analysis through data reduction, data display, and conclusion drawing or verification. The study results reveal that Islamic religious education is less successful because parents still view that schools only carry out the task of educating children. Parental attention to children is only in the form of fulfilling material needs such as clothing, food, and board needs. At the same time, the problem of moral formation and development is left entirely to the school. In addition, because it underestimates the existence of Islamic religious education lessons, it is a lesson that is not too important and easy to learn without having to think.